Quantitative and qualitative transcriptome analysis of four industrial strains of Claviceps purpurea with respect to ergot alkaloid production - Majeská Čudejková, Mária; Vojta, Petr; Valík, Josef; Galuszka, Petr (New biotechnology, 2016)
The fungus Claviceps purpurea is a biotrophic phytopathogen widely used in the pharmaceutical industry for its ability to produce ergot alkaloids (EAs). The fungus attacks unfertilized ovaries of grasses and forms sclerotia, which represent the only type of tissue where the synthesis of EAs occurs. The biosynthetic pathway of EAs has been extensively studied; however, little is known concerning its regulation. Here, we present the quantitative transcriptome analysis of the sclerotial and mycelial tissues providing a comprehensive view of transcriptional differences between the tissues that produce EAs and those that do not produce EAs and the pathogenic and non-pathogenic lifestyle. The results indicate metabolic changes coupled with sclerotial differentiation, which are likely needed as initiation factors for EA biosynthesis. One of the promising factors seems to be oxidative stress. Here, we focus on the identification of putative transcription factors and regulators involved in sclerotial differentiation, which might be involved in EA biosynthesis. To shed more light on the regulation of EA composition, whole transcriptome analysis of four industrial strains differing in their alkaloid spectra was performed. The results support the hypothesis proposing the composition of the amino acid pool in sclerotia to be an important factor regulating the final structure of the ergopeptines produced by Claviceps purpurea.
Keywords: Fungal Proteins; oxidační stres; sekvenční homologie aminokyselin; Peptide Synthases; námelové alkaloidy; Sequence Homology, Amino Acid; jednonukleotidový polymorfismus; sekvence aminokyselin; Genes, Fungal; Oxidative Stress; Polymorphism, Single Nucleotide; Amino Acid Sequence; stanovení celkové genové exprese; Claviceps; biotechnologie; geny hub; fungální proteiny; průmyslová mikrobiologie; exprese genu; Industrial Microbiology; Biotechnology; Ergot Alkaloids; Gene Expression Profiling; Gene Expression; peptidsynthasy